Alienation and emancipation at the university through performing arts - Ramiro Tau; Laure Kloetzer; Aneth Sacher; Anna Zolotareva; Yemariam Abebayehu (SCENARIO: Journal for Performative Teaching, Learning, Research)
This paper, co-written by three students and two lecturers of a master’s course called "Arts-based Approaches to Research and Teaching", focuses on the way in which the performing arts can contribute to the identification and definition of a scholarly research question. Based on a discussion of the phenomenon of learners' alienation in formal education systems, and its restrictive effects frequently pointed out in the specialized literature, we address the problem of the opening towards autonomy in the definition of an original research problem. To this end, the article will (1) introduce our theoretical reflections, discussing the issues on the phenomenon of alienation, emancipation and creation of knowledge within the university setting; (2) explain the structure of the course, with a focus on the place of performing arts in the curriculum; (3) present three vignettes displaying three cases of elaboration and reflection by participant students; (4) offer a final discussion and conclusion on the potential of performing arts to “shake up” or “destabilise” the usual alienation experienced by students regarding the appropriation and creation of knowledge at the university.